2015
DOI: 10.5152/iao.2014.500
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Myringoplasty in Wet and Dry Ears

Abstract: OBJECTIVE:To determine if the wet ear at time of surgery adversely affects the success rate of myringoplasty operations. MATERIALS and METHODS:A total of 46 wet ears (with mucoid discharge) and 52 dry ears (at least 1 month before surgery) with mucosal chronic suppurative otitis media were operated on by myringoplasty. Graft take and hearing gain rates 6 months after surgery were calculated for both groups and compared. RESULTS:The graft take rate was 87% for the wet ear group and 90.4% for the dry ear group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The p value was 0.665 which was statistically insignificant. 11 Shankar et al observed success rate of 88% in the dry ear group and 80% in the wet ear group (p=-0.324) and concluded that success rate is not influenced by the presence of ear discharge at the time of surgery. 12 The mean pre-operative pure tone audiometry (PTA) in group I was 30.57±7.80 dB while post-operative PTA was 20.68±8.22 dB with a mean hearing gain of 9.89 dB.…”
Section: Discussionmentioning
confidence: 99%
“…The p value was 0.665 which was statistically insignificant. 11 Shankar et al observed success rate of 88% in the dry ear group and 80% in the wet ear group (p=-0.324) and concluded that success rate is not influenced by the presence of ear discharge at the time of surgery. 12 The mean pre-operative pure tone audiometry (PTA) in group I was 30.57±7.80 dB while post-operative PTA was 20.68±8.22 dB with a mean hearing gain of 9.89 dB.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Sameh Hosny et al, hearing gain rate of 91.3% in wet ears and 92.3% in dry ears was seen and these differences were not statistically significant. 4 Hatice Emir et al found that post-operative hearing gain was 47.3% in dry ears and 40.7% in wet ears. 5 Benjamin D et al found post-operative hearing gain for dry and wet ear were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies comparable to this study have shown that presence of ear discharge at the time of surgery has no significant bearing on the results of myringoplasty. 7,[9][10][11][12] A comparison of graft uptake of this study with other studies is given in Table 2. Mean hearing gain observed in wet and dry ears were 3.43 dB and 3.85 dB respectively.…”
Section: Discussionmentioning
confidence: 95%